2016
DOI: 10.1017/s094073911600028x
|View full text |Cite
|
Sign up to set email alerts
|

False Closure? Known Unknowns in Repatriated Antiquities Cases

Abstract: Abstract:Based on research into the confiscated photographic and document archives in the hands of the top antiquities dealers (Robin Symes-Christos Michaelides, Robert Hecht, Giacomo Medici, and Gianfranco Becchina), so far more than 250 looted and smuggled masterpieces have been repatriated from the most reputable North American museums, private collections, and galleries, mainly to the Italian and the Greek states. Most of these repatriations were advertised in the press as voluntary action by the instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…En muchas ocasiones se han adoptado acuerdos una vez que ya había comenzado el proceso judicial que ejercía presión sobre las partes (Stamatoudi 2016: 435). De hecho, se ha sugerido que en algunos casos los museos han adoptado acuerdos de devolución para evitar verse obligados a revelar información sobre sus adquisiciones durante un proceso judicial, algo que podría suponerles más solicitudes de devolución de bienes patrimoniales (Tsirogiannis 2016). El uso de las ADR en este ámbito claramente dista de ser perfecto pero es una oportunidad tanto para recuperar unos bienes arqueológicos expoliados como para, en el proceso, generar acuerdos más amplios de colaboración.…”
Section: Mediación Y Las Adr En El Contexto Del Expolio Y El Tráfico De Bienes Arqueológicos: Fórmulas Actuales En El áMbito Internacionaunclassified
“…En muchas ocasiones se han adoptado acuerdos una vez que ya había comenzado el proceso judicial que ejercía presión sobre las partes (Stamatoudi 2016: 435). De hecho, se ha sugerido que en algunos casos los museos han adoptado acuerdos de devolución para evitar verse obligados a revelar información sobre sus adquisiciones durante un proceso judicial, algo que podría suponerles más solicitudes de devolución de bienes patrimoniales (Tsirogiannis 2016). El uso de las ADR en este ámbito claramente dista de ser perfecto pero es una oportunidad tanto para recuperar unos bienes arqueológicos expoliados como para, en el proceso, generar acuerdos más amplios de colaboración.…”
Section: Mediación Y Las Adr En El Contexto Del Expolio Y El Tráfico De Bienes Arqueológicos: Fórmulas Actuales En El áMbito Internacionaunclassified
“…However, the possibilities have almost been exhausted and it has proven ineffective in cases of new pieces placed on the market, usually from war-torn Middle Eastern countries, especially Syria. Furthermore, Tsirogiannis (2016) has demonstrated that the mere presence of photographs in files seized by the Italian police from intermediaries and traffickers, in the first decade of this century, can lead to errors in the attribution of provenience. This would seem to be the case of the sculpture of the wife of Emperor Adrian, Vibia Sabina, returned by the Fine Arts Museum of Boston to the Italian government, which alleged the existence of photos of this work shortly after its clandestine find in the G. Medici archive, when it is now known that it is from Turkey.…”
Section: Falsification Of Provenience and Collecting Historymentioning
confidence: 99%
“…I3xiWuPH/10180/8548028/?redirect=http%3A%2F%2Fwww.interior.gob.es%2Fes%2Fportada%3Fp_ of almost been exhausted and it has proven ineffective in cases of new pieces placed on the market, usually from war-torn Middle Eastern countries, especially Syria. Furthermore, Tsirogiannis (2016) has demonstrated that the mere presence of photographs in files seized by the Italian police from intermediaries and traffickers, in the first decade of this century, can lead to errors in the attribution of provenience. This would seem to be the case of the sculpture of the wife of Emperor Adrian, Vibia Sabina, returned by the Fine Arts Museum of Boston to the Italian government, which alleged the existence of photos of this work shortly after its clandestine find in the G. Medici archive, when it is now known that it is from Turkey.…”
Section: Falsification Of Provenience and Collecting Historymentioning
confidence: 99%